Inklusivisme Guru di Sekolah Dasar Ihwal Pendidikan Agama untuk Kelompok Minoritas - Bazikh, Moh. Rofqil (Fahima, 2024)
According to the law (UU) and Government Regulation (PP) religious education is a necessity in school institutions. The problematic thing is when there is a student who has a different background and becomes a minority. In this position, the school has to give religious education by students' religious beliefs. Unfortunately, the reality is not like that. This research aims to see how inclusive the teacher in the grassroots regarding religious education for minorities. The target of this research is two Elementary Schools in Sedayugunung village, Besuki subdistrict, Tulungagung regency. Nine teachers agreed to interview about this topic. The type of this research is qualitative-descriptive based on field research. Two theories are used to analyze the findings of the interview. First, contact theory was initiated by Gordon Allport. Second, the threefold typology was initiated by Alan Race. The finding shows the inclusivism of teachers toward other religious communities, especially to hold religious education according to student religious belief. This attitude of teachers is categorized into inclusive typology within the view of religious groups. The teacher’s attitude is constructed by two things, digital world existence and interaction with another religious believer. In the end, this research conclusion suits to theory contact dictum that meeting with another religious believer can reduce prejudice.